2009
DOI: 10.1016/j.juro.2009.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Health Related Quality of Life in Patients With Spina Bifida: A Prospective Assessment Before and After Lower Urinary Tract Reconstruction

Abstract: Despite improvement in some question items we did not note an improvement in overall quality of life following reconstruction. Correcting only 1 system in a profound multisystem disability may be insufficient to improve health related quality of life or perhaps only caregiver quality of life is improved. The impact of lower urinary tract reconstruction on quality of life in patients with spina bifida requires further assessment before improvements are assumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 17 publications
0
43
0
1
Order By: Relevance
“…Lemelle et al (23) have shown that functional improvement in either continence or walking status is not associated with enhanced QoL. This phenomenon has also demonstrated by MacNeily et al (14), who showed that despite improvement of lower urinary tract symptoms after lower urinary tract reconstruction, HRQoL remains the same. MacNeily et al (14) postulate that this may be due to increased burden placed on the patient to attain continence, the imperfect continence success rates and/or the morbidity of the treatment options.…”
Section: Discussionmentioning
confidence: 75%
“…Lemelle et al (23) have shown that functional improvement in either continence or walking status is not associated with enhanced QoL. This phenomenon has also demonstrated by MacNeily et al (14), who showed that despite improvement of lower urinary tract symptoms after lower urinary tract reconstruction, HRQoL remains the same. MacNeily et al (14) postulate that this may be due to increased burden placed on the patient to attain continence, the imperfect continence success rates and/or the morbidity of the treatment options.…”
Section: Discussionmentioning
confidence: 75%
“…As the impact of fecal incontinence is weighed with other global QOL factors, the benefit to global QOL may be less significant. This phenomenon is highlighted by the work of MacNeily et al 16 (2009) that showed no global QOL benefit to lower urinary tract reconstruction in the spina bifida population.…”
Section: Discussionmentioning
confidence: 99%
“…This impact has been questioned recently when MacNeily et al failed to show any improvement in overall QOL following bladder augmentation in SB patients (16,17). Importantly, the QOL instrument used by MacNeily et al does not specifically ascertain the impact of fecal or urinary continence.…”
Section: Quality Of Lifementioning
confidence: 99%